2017
DOI: 10.1002/chem.201703817
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Activity of π‐Acid Catalysts using a 7‐Alkynyl Cycloheptatriene

Abstract: A compound that isomerizes into distinct products depending on the particular Lewis acid or Brønsted acid catalyst used is disclosed. One product can only be obtained with the softest π-acids, such as Au, Pt, Ga, or In complexes. Another is formed only with harder π-acids incorporating Ag or Cu salts. The formation of the third category requires even harder π-acids or protons. This simple benchmark reaction allows for prediction of the category of transformations that can be catalyzed by a new complex. It also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…This transformation gives an easy access to functionalized alkenes or alkanes . As previously described by Kitagawa and more recently by us,[11a] 7‐alkynylcycloheptatrienes can rearrange into phenylallenes. Therefore, in the presence of a suitable catalyst, the pendant aryl moiety could then promote the hydroarylation of the allene moiety.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…This transformation gives an easy access to functionalized alkenes or alkanes . As previously described by Kitagawa and more recently by us,[11a] 7‐alkynylcycloheptatrienes can rearrange into phenylallenes. Therefore, in the presence of a suitable catalyst, the pendant aryl moiety could then promote the hydroarylation of the allene moiety.…”
Section: Resultsmentioning
confidence: 70%
“…Under hard Lewis acidic conditions, the allene can be trapped by a pendant aryl group to give a hydroarylation product (Equ. 4) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In DCE, as olvent that can give rise to superacids, such as HSbF 6 ,i nt he presence of AgSbF 6 or SbF 5 , [8,9 ] or by using HNTf 2 ,t he conversion of 4 into the tricyclic compound 5 is observed with time, whichc orresponds to the hydroarylation of the styrene moiety through ab enzylic carbocation. [5] One interest of this test is to identify new soft p-acids, as we did in the gallium(I) and indium(I) series. [5,10] Another interesti s to show the efficiency of an anion exchange.…”
mentioning
confidence: 99%
“…[2a, 3c] The classification of Lewis acids between the softest ones,whichwill be good for mediating enynecycloisomerizations, and harder ones,w hichw ill be more potent for CÀC p bond functionalization through classical carbocations, can be easily made by using the cycloheptatriene test that we developed. [5] As described by Echavarren et al,7 -alkynylcycloheptatrienes are treated like enynesb yg old(I)c omplexes (Scheme 1, reaction2). [6] Likewise, we reported that the reaction of compound 1 with catalysts of the gold, platinum, mercury,g allium and indium seriesl eads to its skeletal reorganization into the regioisomeric indenes 2 and 3 in 1,2-dichloroethane (DCE) or toluene (Scheme 2).…”
mentioning
confidence: 99%